Estudio de mercado para la comercialización del queso casero de la microempresa “Rico Queso” en el cantón San Jacinto de Buena Fe, año 2014 - Chichande Anzules, Karina Vanessa (2015)
The market study for the marketing of home cheese made by the microenterprise “Rico Queso” in the borough of San Jacinto in the city of Buena Fe, year 2014, includes the evaluation of the supply which is carried out through the analysis of the competition considering the following variables: characteristics and origin of the product, the market price, and the presentation and quality of the product that is currently offered. The results obtained in the survey, with the intention of establishing the purchasing power of consumers, their behavior in the market and factors that can affect the results obtained, were considered for assessment of the demand for the cheese. The study is complemented with an internal and external analysis of "Rico Queso" microenterprise through the SWOT matrix and the establishment of strategic alternatives to compare the strengths and weaknesses with the opportunities and threats. The results are based on the proposal which consists in the design of sales strategies that encourage the commercialization of this product in the canton San Jacinto de Buena Fe. To meet the objectives, product positioning strategies were outlined for “Rico Queso” as well as developing distribution strategies for the delivery of orders. In addition, the sales budget and the profitability of its implementation were set.